The volume of infusion fluids correlates with treatment outcomes in critically ill trauma patients - Wrzosek, Anna; Drygalski, Tomasz; Garlicki, Jarosław; Woroń, Jarosław; Szpunar, Wojciech; Polak, Maciej; Droś, Jakub; Wordliczek, Jerzy; Zajączkowska, Renata (Frontiers in Medicine, 2023)
Appropriate fluid management is essential in the treatment of critically ill trauma patients. Both insufficient and excessive fluid volume can be associated with worse outcomes. Intensive fluid resuscitation is a crucial element of early resuscitation in trauma; however, excessive fluid infusion may lead to fluid accumulation and consequent complications such as pulmonary oedema, cardiac failure, impaired bowel function, and delayed wound healing. The aim of this study was to examine the volumes of fluids infused in critically ill trauma patients during the first hours and days of treatment and their relationship to survival and outcomes. Methods: We retrospectively screened records of all consecutive patients admitted to the ICU from the beginning of 2019 to the end of 2020. All adults who were admitted to ICU after trauma and were hospitalized for a minimum of two days were included in the study. We used multivariate regression analysis models to assess a relationship between volume of infused fluid or fluid balance, age, ISS or APACHE II score, and mortality. We also compared volumes of fluids in survivors and non-survivors including additional analyses in subgroups depending on disease severity (ISS score, APPACHE II score), blood loss, and age. Results: 52 patients met the inclusion criteria for the study. The volume of infused fluids and fluid balance were positively correlated with mortality, complication rate, time on mechanical ventilation, length of stay in the ICU, INR, and APTT. Fluid volumes were significantly higher in non-survivors than in survivors at the and of the second day of ICU stay (2.77 vs 2.14 ml/kg/h) and non-survivors had a highly positive fluid balance (6.21 compared with 2.48 litres in survivors). Conclusions: In critically ill trauma patients, worse outcomes were associated with higher volumes of infusion fluids and a more positive fluid balance. Although fluid resuscitation is lifesaving, especially in the first hours after trauma, fluid infusion should be limited to a necessary minimum to avoid fluid overload and its negative consequences.